The incidence of early onset colorectal cancer in Aotearoa New Zealand: 2000–2020 - Oliver Waddell; John Pearson; Andrew McCombie; Harriet Marshall; Rachel Purcell; Jacqueline Keenan; Tamara Glyn; Frank Frizelle (BMC Cancer, 2024)
Abstract Background The incidence of early-onset colorectal cancer (EOCRC), diagnosed before age 50, has been rising in many countries in the past few decades. This study aims to evaluate this trend in Aotearoa New Zealand and assess its impact on Māori. Methods Crude incidence and age-standardized incidence of colorectal cancer (CRC) was analyzed from all new cases from the Aotearoa New Zealand national cancer registry for the period 2000–2020. Trends were estimated by sex, ethnicity, age group and location of cancer and projections made to 2040. Results Between 2000 and 2020, there were a total of 56,761 cases of CRC diagnosed in Aotearoa New Zealand, 3,702 of these being EOCRC, with age-standardized incidence decreasing significantly (P = 8.2 × 10− 80) from 61.0 to 47.3 cases per 100,000. EOCRC incidence increased on average by 26% per decade (incidence rate ratio (IRR) 1.26, p = < 0.0001) at all sites (proximal colon, distal colon and rectum), while the incidence in those aged 50–79 years decreased on average by 18% per decade (IRR 0.82, p = < 0.0005), again across all sites. There was no significant average change in CRC incidence in those over 80 years. In Māori, there was no significant change in age-standardized incidence. There was however a significant increase in crude incidence rates (IRR 1.28, p = < 0.0005) driven by significant increases in EOCRC (IRR1.36, p = < 0.0005). By 2040, we predict the incidence of EOCRC will have risen from 8.00 to 14.9 per 100,000 (6.33 to 10.00 per 100,000 in Māori). However, due to the aging population an estimated 43.0% of all CRC cases will be diagnosed in those over 80 years of age (45.9% over 70 years of age in Māori). Conclusion The age-standardized incidence of CRC from 2000 to 2020 decreased in Aotearoa New Zealand, but not for Māori. The incidence of EOCRC over the same period continues to rise, and at a faster rate in Māori. However, with the ageing of the population in Aotearoa New Zealand, and for Māori, CRC in the elderly will continue to dominate case numbers.